Synthesis of ortho-substituted nitroaromatics via improved Negishi coupling conditions - Tuttle, Jamison B.; Azzarelli, Joseph M.; Bechle, Bruce M.; Dounay, Amy B.; Evrard, Edelweiss; Gan, Xinmin; Ghosh, Somraj; Henderson, Jaclyn; Kim, Ji-Young; Parikh, Vinod D.; Verhoest, Patrick R. (Tetrahedron letters, 2011)
We describe modified Negishi coupling conditions that allow improved access to ortho-nitrophenylalanine derivatives. These useful amino acid intermediates can be further elaborated into biologically active lactams and cyclic hydroxamic acid targets.